Systemic action of Nikel - Antoszczyk, Grażyna; Obtułowicz, Krystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Nickel is the most common substance in our environment. It is known as commonest couse of allergic contact dermatitis. Similar to chromium, cobalt and zinc, nickel may also be a cause of allergy in the upper and lower airways. It may lead to diseases described as ”hard metal asthma” and ”hard metal rhinitis”. The study aimed to determine the prevelance of systemic nickel induced reaction in patients sensitized to nickel and suffering from atopic dermatitis, allergic contact dermatitis and urticaria. In all patients during remission of symptoms were performed patch tests with European Standard contact allergens, serial dilution patch tests and oral provocation test with increasing doses of nickel sulphate. Our studies indicate that oral nickel challenge can provoke symptoms of skin allergy type I and type IV.